Constructing Gender Authority in Modern Islam: A Sociology of Knowledge Analysis of Yusuf al-Qaradhawi and Nazaruddin Umar on Women’s Political Participation - Kamal, Aulia (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
This study examines how religious authority shapes gender discourse in contemporary Muslim society through a comparative analysis of Yusuf Al-Qaradhawi and Nazaruddin Umar's thoughts on women's political participation. Using a sociology of knowledge framework integrated with Bourdieu's field theory and Giddens' structuration theory, this study answers three questions: how is epistemic authority built in different field positions, how do socio-religious structures shape intellectual production, and do different approaches contribute to the transformation of gender discourse? The analysis reveals three main findings. First, both scholars successfully established credible positions that enabled women's eligibility to run for president through contrasting strategies: Al-Qaradhawi accumulated orthodox reformist capital in the field of transnational scholars, enabling broad acceptance while setting conditions (Islamic dress, family priorities, husband's permission); Umar developed a comprehensive gender hermeneutics at the boundaries of academia and government, enabling unconditional participation based solely on competence. Second, field positions tangibly shape interpretive possibilities; Al-Qaradhawi's ulama habitus produces incremental modifications, while Umar's academic-modern habitus enables radical hermeneutic interventions, yet both demonstrate reflective agency in negotiating patriarchal structures. Third, both approaches contribute complementarily but incompletely to transformation: Al-Qaradhawi achieves broader acceptance through moderate reformism; Umar offers a stronger theological foundation through the principle of equality. Both maintain skepticism toward classical caliphate, indicating uneven transformation across institutional domains. The integration of Bourdieusian and Giddensian frameworks explains how discourse operates simultaneously as a mechanism of structural reproduction and a site of transformative possibility. This study concludes that religious knowledge functions as a socially embedded practice, facilitating partial rather than total transformation of patriarchal structures.